(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article provides a comprehensive study of the relationship between the individual and society in the teachings of Tasawwuf (Sufism). It analyzes the concept of the self in Sufi tradition, the paths to spiritual perfection through the training of the nafs (soul), and the significance of this process in social life. Based on the views of prominent mystics such as Al-Ghazali, Ibn Arabi, and Bahauddin Naqshband, the article highlights the social responsibility of the individual and their harmony with society. In a contemporary context, the role of Sufi values in the spiritual development of the individual and the sustainable progress of society is demonstrated. The research findings confirm that the teachings of Tasawwuf remain highly relevant for spiritual renewal and social stability today.